The Influence Of Mental Health Conditions Of Indonesian Teenagers To Realize A Golden Indonesia 2045 - Meilva Farrah Dilla; M Khalid Al Aziz; Nazhifa Yasmin Amri; Nabira Mutiara; Miftahul Jannah (SEAN Institute, 2024)
The vision of